Nutritional Supplements in Sports and Exercise - Greenwood, Mike; Kalman, Douglas; Antonio, Jose (Humana Press : Imprint: Humana, 2008)
In the ever-growing field of sports nutrition and nutritional supplementation, it is imperative to have a comprehensive and extensive guide, which is exactly what Nutritional Supplements in Sports and Exercise provides. The editors and authors have skillfully structured their research and findings as they deliver an accessible wealth of knowledge to the general population, while also maintaining academic and professional integrity through quality based and advanced scientific research, which renders it useful in the professional environment by sports nutritionists, exercise physiologists, strength and conditioning/personal trainers, athletic trainers, registered dietitians, college/ professional sports affiliates, and academic programs. Not only does Nutritional Supplements in Sports and Exercise significantly cover the physical aspects of supplement usage, but it also expands its breadth as it notes the psychological effects upon users and discusses its various governmental regulations, and attempts to understand the future of nutritional supplements as the industry continues its likely growth. Nutritional Supplements in Sports and Exercise covers a timely subject, and offers interested readers knowledgeable insight into a rising industry plagued by concerns and question.